Analisis Hukum tentang Tanggung Jawab dokter dalam Kasus Malpraktik Medis di Indonesia - Gina Musfirah; Syamsuddin Syamsuddin (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2026)
The relationship between a doctor and a patient is a therapeutic one based on trust and maximum effort (inspanningsverbintenis), not on a guaranteed outcome (resultaatsverbintenis). In practice, disputes often arise due to alleged medical negligence that harms patients, commonly known as malpractice. Given that medical malpractice is a widely researched topic, this study provides novelty by explicitly focusing its analysis on the shift toward a restorative justice paradigm as mandated by Law Number 17 of 2023 concerning Health. This study aims to analyze the forms of legal liability of doctors in medical malpractice cases in Indonesia from the perspectives of civil, criminal, and administrative law. The research employs a normative juridical method with statutory, conceptual, and jurisprudential approaches. The results indicate that doctors' liabilities encompass material and immaterial compensation (civil), license revocation sanctions (administrative), and imprisonment as a last resort (ultimum remedium) if gross negligence is proven. Crucially, the proof of malpractice must be clearly distinguished from unavoidable medical risks that occur despite adherence to professional standards.